1975
DOI: 10.1016/0022-1902(75)80915-8
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer spectra of tetravalent lanthanide ions in oxides

Abstract: Abstract--The charge-transfer spectra of Ce 4~, Pr "+ and Yb "+ in a number of oxides are reported. It is noted that the position of the first charge-transfer band is fixed for the metal ion in an oxygen coordination of V1, but varies in VIII coordination as a function of the host lattice. It is argued that this variation is inherent to the VIII coordination itself.INTRODUCTION IN THE past decade quite some work has been done on charge transfer (c.t.) transitions in molecular or ionic groups in which an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 15 publications
10
61
0
1
Order By: Relevance
“…The position and the width of this band are similar to those observed for Ce4+ and other 4+ charged rare earth ions in several oxide lattices [5,6]. The fact that extra absorption at wavelengths c350 nm appears after annealing in an 0 2 atmosphere supports the assignment of the 276 nm absorption band to Ce4+.…”
Section: Discussionsupporting
confidence: 79%
“…The position and the width of this band are similar to those observed for Ce4+ and other 4+ charged rare earth ions in several oxide lattices [5,6]. The fact that extra absorption at wavelengths c350 nm appears after annealing in an 0 2 atmosphere supports the assignment of the 276 nm absorption band to Ce4+.…”
Section: Discussionsupporting
confidence: 79%
“…A clear example of this is the position of the charge-transfer absorption band of the Eu3+ ion in six coordination in mixed-metal oxides. On experimental and theoretical grounds this position is expected to be independent of the Eu3+-02-distance (32). From spectroscopic measurements it is observed at (42 +-1)103 cm-i.…”
Section: Charge Effectsmentioning
confidence: 82%
“…5) the band at 3351x0 Is probably due to the 4f-5d transition on Ce3+. It may be suggested that the broad absorption band is due to a Ce 4+ charge-transfer transition, lut these are usually situated at rmch higher energy [18]. Hanver, there is a more obvious possibility.…”
Section: Resultsmentioning
confidence: 99%